The Comparison of Short- and Long-Term Outcomes for Laparoscopic Versus Open Gastrectomy for Patients With Advanced Gastric Cancer: A Meta-Analysis of Randomized Controlled Trials - Jiang, Jinyan; Ye, Guanxiong; Wang, Jun; Xu, Xiaoya; Zhang, Kai; Wang, Shi (Frontiers in Oncology, 2022)
Abstracts Objectives: The effect of laparoscopic gastrectomy (LG) for the treatment of advanced gastric cancer (AGC) is still controversial. The aim of this meta-analysis was to contrast the short- and long-term outcomes of laparoscopic versus conventional open gastrectomy (OG) for patients with AGC. Methods: Databases including PubMed, Embase, Scopus, and Cochrane Library were systematically searched until December 2021 for randomized controlled trials enrolled patients undergoing LG or OG for the treatment of AGC. Short-term outcomes were overall postoperative complications, anastomotic leakage, number of retrieved lymph node, surgical time, blood loss, length of hospital stay, and short-term mortality. Long-term outcomes were survival rates at 1, 3, and 5 year. Results: A total of 12 trials involving 4101 patients (2059 in LG group, 2042 in OG group) were included. No effect on overall postoperative complications (OR 0.84, 95%CI 0.67 to 1.05, P=0.12, I2=34%) and anastomotic leakage (OR 1.26, 95%CI 0.82 to 1.95, P=0.30, I2=0%) was found. Compared with open approach, patients receiving LG had fewer blood loss (MD -54.38, 95%CI -78.09 to -30.67, P<0.00001, I2=90%) and shorter length of hospital stay (MD -1.25, 95%CI -2.08 to -0.42, P=0.003, I2=86%). However, the LG was associated with fewer number of retrieved lymph node (MD -1.02, 95%CI -1.77 to -0.27, P=0.008, I2=0%) and longer surgical time (MD 40.87, 95%CI 20.37 to 54.44, P<0.00001, I2=94%). Furthermore, there were no differences between LG and OG groups in short-term mortality and survival rate at 1-, 3-, and 5-year. Conclusions: LG offers improved short-term outcomes including shorter hospital stays and fewer blood loss, with comparable postoperative complications, short-term mortality and survival rate at 1-, 3-, and 5-year when compared to open approach. Our results support the implementation of LG in patients with AGC.